ECONOMIC ANALYSIS OF CONDITION BASED MAINTENANCE - Camci, Fatih; Berdinyaz, Ashyrmuhammet; Sevkli, Mehmet; Baskan, Saim (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
<span style="font-size: 10pt; color: black; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Maintenance is an inevitable reality in industry. Not only its close relationship with safety but also its direct and indirect costs make it attractive for companies and researchers. Initially, the focus for maintenance research was on the periodic maintenance, mainly targeting the identification optimum maintenance period. A new concept of maintenance, Condition Based Maintenance (CBM), is now under examination with many applied industrial examples. CBM attracts researchers and industry in recent years with the ability to decrease system operating & support cost, increase availability and safety. Even though CBM leads to many benefits, initial investment cost and possible uncertainties might cause hesitation. A detailed economic analysis of CBM that helps decision makers to analyze the benefits of CBM for a given system is needed. This paper presents an economic analysis method for CBM that helps the decision makers on investment decisions about CBM. The presented method aims to answer detailed questions about investment using the sensitivity analysis such as return on investment, required accuracy or false alarm levels from a CBM module, etc. The presented method uses reliability, system, and economic parameters for cost calculation. Two case studies in turnouts in railway systems are presented in the paper.